2014
DOI: 10.1095/biolreprod.114.119503
|View full text |Cite
|
Sign up to set email alerts
|

LewisX-Containing Glycans on the Porcine Oviductal Epithelium Contribute to Formation of the Sperm Reservoir1

Abstract: In many mammals, after semen deposition, a subpopulation of the sperm is transported to the lower oviduct, or isthmus, to form a functional sperm reservoir that provides sperm to fertilize oocytes. The precise molecular interactions that allow formation of this reservoir are unclear. It is proposed that binding of sperm receptors (lectins) to their oviductal cell ligands is accomplished by glycans. Previous results indicated that Lewis trisaccharides are present in glycosphingolipids and O- and N-linked glycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…Furthermore, Lewis a tagged by conjugation to fluorescein-labeled polyacrylamide bound to the heads of live bull sperm (Suarez et al 1998). Similarly, boar sperm bind to Lewis x trisaccharide, which contains fucose in an alpha 1-3 linkage to N-acetylglucosamine and has been localized to the surfaces of epithelium in the porcine oviductal isthmus (Machado et al 2014). Altogether, these characterizations of oviductal receptors for sperm indicate that carbohydrates are part of the sperm binding site, although the particular carbohydrates vary among species.…”
Section: Molecular Interactionsmentioning
confidence: 99%
“…Furthermore, Lewis a tagged by conjugation to fluorescein-labeled polyacrylamide bound to the heads of live bull sperm (Suarez et al 1998). Similarly, boar sperm bind to Lewis x trisaccharide, which contains fucose in an alpha 1-3 linkage to N-acetylglucosamine and has been localized to the surfaces of epithelium in the porcine oviductal isthmus (Machado et al 2014). Altogether, these characterizations of oviductal receptors for sperm indicate that carbohydrates are part of the sperm binding site, although the particular carbohydrates vary among species.…”
Section: Molecular Interactionsmentioning
confidence: 99%
“…A recent study using an array with 377 glycans, a much larger number than has been examined previously, has demonstrated that porcine spermatozoa recognize with high affinity, carbohydrate structures containing Lewis X (Le X ) or biantennary 6-sialylated N -acetyllactosamine (bi-SiaLN) motifs and that recognition of these motifs mediates porcine sperm binding to the oviduct cell aggregates (Kadirvel et al ., 2012; Machado et al ., 2014). Lewis X is a trisaccharide formed by the monosaccharides N -acetyl glucosamine, galactose and fucose.…”
Section: Introductionmentioning
confidence: 99%
“…a2-3-linked sialic acids expressed on the luminal surface of NCs could have a role in the specific functions of the ovine isthmus epithelium. Indeed, sialoglycoconjugates on the epithelial surface are necessary for the head of sperm to bind to the apical side in rat [51] and pig [52,53]. The apical side of the epithelial cells is involved in the sperm-oviduct interaction by species-specific sugars: galactose in horses [54], fucose in cattles [55,56], and galactose, mannose, Neu5Aca2-6Gal, Lewis  antigen in pigs [53].…”
Section: Discussionmentioning
confidence: 99%